2009
DOI: 10.1177/147323000903700111
|View full text |Cite
|
Sign up to set email alerts
|

Small Dense Low-Density Lipoprotein Concentration and Oxidative Susceptibility Changes after Consumption of Soybean Oil, Rice Bran Oil, Palm Oil and Mixed Rice Bran/Palm Oil in Hypercholesterolaemic Women

Abstract: The effects of a diet containing soybean oil (SBO), rice bran oil (RBO), palm oil (PO) or a RBO/PO (3:1) mixture on the composition and oxidation of small dense low-density lipoproteins (sdLDL) in 16 hypercholesterolaemic women were investigated. During the 8-week control period, participants consumed a free-choice weight-maintaining diet comprising carbohydrate (55% energy), protein (15% energy) and fat (30% energy) with < 300 mg/day of cholesterol. During each 10-week study period, participants consumed this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…Even for the more robust theory on atherogenicity of sdLDL, a predominance of very large rather than sdLDL has been reported with increased CVR [22], 3) The few studies reporting longitudinal changes of lipoprotein subfractions following a lifestyle intervention (diet, physical activity) describe relatively acute [23] or short term responses [13,24-26], 4) lack direct measures of atherogenicity inside the walls or arteries [13,23-26], 5) provide limited selections of lipoprotein subfractions [13,23-26], and 6) are not reported in populations with MetS [13,23-26]. …”
Section: Introductionmentioning
confidence: 99%
“…Even for the more robust theory on atherogenicity of sdLDL, a predominance of very large rather than sdLDL has been reported with increased CVR [22], 3) The few studies reporting longitudinal changes of lipoprotein subfractions following a lifestyle intervention (diet, physical activity) describe relatively acute [23] or short term responses [13,24-26], 4) lack direct measures of atherogenicity inside the walls or arteries [13,23-26], 5) provide limited selections of lipoprotein subfractions [13,23-26], and 6) are not reported in populations with MetS [13,23-26]. …”
Section: Introductionmentioning
confidence: 99%
“…At the end of the study after stanol supplementation the number of total LDL particles decreased, but sdLDL particles did not differ compared with baseline [51]. Utarwuthipong et al [52] also reported a study of 16 hyperlipidaemic women who were recommended a National Cholesterol Expert Panel diet (55% carbohydrate, 15% protein, 30% fat, < 300 mg/day of cholesterol) as a run in baseline diet for 8 weeks. All participants were subsequently randomized into four treatment groups to take either diet plus SBO (soybean oil, 20% of total energy), or diet plus RBO (rice bran oil, 20% of total energy) or diet plus PO (palm oil, 20% of total energy) or diet plus RBO/PO (20% of total energy as mixture of (3:1) RBO/PO).…”
Section: Phytosterols and Vegetable Oilsmentioning
confidence: 97%
“…A lot of controversy overwhelms the high content of saturated fatty acids, especially palmitic acid (16:0) in palm oil (Mukherjee & Mitra, 2009) and environmental issues associated with palm oil production (Maragoni et al, 2017). There is scientific evidence showing that palm oil may increase some potential heart disease risk factors like low-density lipoprotein (LDL) cholesterol levels (Karupaiah et al, 2016;Utarwuthipong, Komindr, Pakpeankitvatana, Songchitsomboon, & Thongmuang, 2009;Vega-López, Ausman, Jalbert, Erkkilä, & Lichtenstein, 2006). Also, recent studies by Clemens, Hayes, Sundram, and Pressman (2017) confirmed, that all seed oil processing, including palm, produces contaminates like 3-MCPD and related chloropropanols that might have toxicological effects in human.…”
Section: Introductionmentioning
confidence: 99%